A case of pancreatic acinar cell carcinoma metastatic to skin - Masahiro Nishikawa (Rare Tumors, 2010)
We report a rare case of pancreatic acinar cell carcinoma with widespread metastases in a 68-year-old woman who presented with subcutaneous nodules as the initial symptom. Computed tomography showed a pancreatic mass with hepatic tumors and enlarged lymph nodes besides ring-enhanced subcutaneous nodules. Magnetic resonance diffusion-weighted imaging detected the presence of lesions in other organs. Histological analysis of a colonic polypoid lesion revealed carcinoma with endocrine and acinar differentiation compatible with pancreatic origin. Regrettably, she died of a cerebral infarction without any treatment, and autopsy findings confirmed our diagnosis.